Public Health and Patent Law to Access Medicine in India - Shrivastava, Srishti; Baliarsingh, Jayashree (South Eastern European Journal of Public Health, 2024)
India's 1970 decision to include a process patent regime in its patent legislation is regarded as a reformative step that was a well-considered reaction to internal issues including the nation's then-current socioeconomic realities. The primary goal of this research project has been to critically analyse the connections among public health, the global intellectual property law, and the availability of necessary medications, with a particular emphasis on India. The study's main focus is the persistent issue of developing and least developed nations' lack of access to reasonably priced medical care in the post-crisis age. This study aims to investigate the inherent barriers to intellectual property that impact medical access, excluding the impact of non-intellectual property impediments such as distribution, infrastructure, quality, and medical facilities. The purpose of this study is to examine how patent law affects drug accessibility while accounting for drug costs.